Term structure of interest rate: an empirical test of the expectation hypothesis on the Malaysian T- Bill Market - Noor Azlan Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 1993)
Interrelationship between short and long term rates is vital in the understanding of interest rate behaviOur expectation hypothesis claims that the yield of the long term instrument is equal to the average of the short term rates that prevail over the long term period. According to the theory, the unobserved future spot rate can be determmed from the observed spot rate. This is possible because the observed rate contains superior information of market expectation. This study investigates the validity of the expectation theory on the Malayswian T bill market for a period of 17 years (1974 - 1990). Regression and correlation analyses are used in testing the hypothesIs. The result supports the validity of the expectatIOn theory. The two expectation models employed, I.e., Perfect-ForesIght Model and Error-Learmng Model, confirm the notzon of expectatIOn hypothesIs, The forward rate Implied by the term structure form as an unbzased estlmate of future spot rate. The validity of the expectatIOn theory in different interest rate environments (declining or increasing) is also tested. The result suggests consistency in validity in all subperiOds. However, the accuracy of the predictiOn increased substantially toward the latter end of the period under study. This reflects the interest rate deregulation process which took place in the Malayszan financi market in recent years.